Isoprenoid compounds from Euphorbia portlandica. X-ray structure of lupeportlandol, a new lupane triterpene - Madureira, AM (2015)
Phytochemical survey of the Me2CO extracts of the whole dried plant Euphorbia portlandica led to the isolation of a new pentacyclic triterpene alcohol, with the lupane skeleton, named lupeportlandol. Its structure was established as 3alpha-hydroxy-19alphaH-lup-20(29)-ene. The known pentacyclic triterpene glutinol and the steroid beta-sitostenone were also isolated. The characterization of the new compound and its acetylated derivative was based on spectroscopic methods and an Xray diffraction analysis. Lupeportlandol acetate was inactive in cytotoxicity assays in vitro against three human tumor cell lines: MCF-7 (breast cancer), NCI-H460 (non-small cell lung cancer) and SF-268 (CNS cancer).